Inhibition of IκB Kinase at 24 Hours After Acute Kidney Injury Improves Recovery of Renal Function and Attenuates Fibrosis. Issue 7 (July 2017) - Johnson, Florence L.; Patel, Nimesh S. A.; Purvis, Gareth S. D.; Chiazza, Fausto; Chen, Jianmin; Sordi, Regina; Hache, Guillaume; Merezhko, Viktoria V.; Collino, Massimo; Yaqoob, Muhammed M.; Thiemermann, Christoph
Abstract : Background: Acute kidney injury (AKI) is a major risk factor for the development of chronic kidney disease. Nuclear factor‐κB is a nuclear transcription factor activated post‐ischemia, responsible for the transcription of proinflammatory proteins. The role of nuclear factor‐κB in the renal fibrosis post‐AKI is unknown. Methods and Results: We used a rat model of AKI caused by unilateral nephrectomy plus contralateral ischemia (30 minutes) and reperfusion injury (up to 28 days) to show impairment of renal function (peak: 24 hours), activation of nuclear factor‐κB (peak: 48 hours), and fibrosis (28 days). In humans, AKI is diagnosed by a rise in serum creatinine. We have discovered that the IκB kinase inhibitor IKK16 (even when given at peak serum creatinine) still improved functional and structural recovery and reduced myofibroblast formation, macrophage infiltration, transforming growth factor‐β expression, and Smad2/3 phosphorylation. AKI resulted in fibrosis within 28 days (Sirius red staining, expression of fibronectin), which was abolished by IKK16. To confirm the efficacy of IKK16 in a more severe model of fibrosis, animals were subject to 14 days of unilateral ureteral obstruction, resulting in tubulointerstitial fibrosis, myofibroblast formation, and macrophage infiltration, all of which were attenuated by IKK16. Conclusions: Inhibition of IκB kinase at peak creatinine improves functional recovery, reduces further injury, and prevents fibrosis.